The accidentals : a novel - Gwin, Minrose (William Morrow, an imprint of HarperCollinsPublishers, 2019)
"Following the death of their mother from a botched backwoods abortion, the McAlister daughters have to cope with the ripple effect of this tragedy as they come of age in 1950s Mississippi and then grow up to face their own impossible choices--an unforgettable, beautiful novel that is threaded throughout with the stories of mothers and daughters in pre-Roe versus Wade America. Life heads down back alleys, takes sharp left turns. Then, one fine day it jumps the track and crashes." In the fall of 1957, Olivia McAlister is living in Opelika, Mississippi, caring for her two girls, June and Grace, and her husband, Holly. She dreams of living a much larger life--seeing the world and returning to her wartime job at a landing boat factory in New Orleans. As she watches over the birds in her yard, Olivia feels like an "accidental"--a migratory bird blown off course. When Olivia becomes pregnant again, she makes a fateful decision, compelling Grace, June, and Holly to cope in different ways. While their father digs up the backyard to build a bomb shelter, desperate to protect his family, Olivia's spinster sister tries to take them all under her wing. But the impact of Olivia's decision reverberates throughout Grace's and June's lives. Grace, caught up in an unconventional love affair, becomes one of the "girls who went away" to have a baby in secret. June, guilt-ridden for her part in exposing Grace's pregnancy, eventually makes an unhappy marriage. Meanwhile Ed Mae Johnson, an African-American care worker in a New Orleans orphanage, is drastically impacted by Grace's choices. As the years go by, their lives intersect in ways that reflect the unpredictable nature of bird flight that lands in accidental locations--and the consolations of imperfect return. Filled with tragedy, humor, joy, and the indomitable strength of women facing the constricted spaces of the 1950s and 60s, The Accidentals is a poignant, timely novel that reminds us of the hope and consolation that can be found in unexpected landings"--